DAMPAK DAN UPAYA PENGENDALIAN SEMBURAN LUMPUR PANAS DI PORONG SIDOARJO - Wijaya, R. Andy Erwin (Geomedia Majalah Ilmiah dan Informasi Kegeografian, 2018)
Abstrak The gas exploration by PT Lapindo Brantas have caused hot mud flow at Porong area. Sidoarjo, East Java. The hot mund flow have flooded some locations i.e. resident, agriculture and industry areas. Contamiation of this hot mud flow have results negative impact to society health, economics and environment. This case of hot mud flow from Banjar Panji-1 well do not be caused by liquid facation after Yogyakarta earthquake but that's because underground blowout. The hot mud flow efforts controlled can be done by snubbing unit, side tracking and relief well. Up to now the hot mud flow not be able stopped. Kata kunci : (lumpur lapindo, hot mud flow, dampak lumpur Porong)